Modulation of GLUT4 and FOXO1 Expression by SH-MSC and Alkaline Water in Experimental Type 2 Diabetes Mellitus - Fatmawati, Dian; Putra, Agung; Setiawan, Eko (Media Publikasi Cendekia Indonesia, 2025)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disorder characterized by insulin resistance, which is associated with the dysregulation of glucose transporter 4 (GLUT4) and forkhead box protein O1 (FOXO1). The secretome from hypoxia-preconditioned mesenchymal stem cells (SH-MSC) and alkaline water have been proposed as potential therapies to modulate these molecular targets and improve glycemic control; however, their combined effects remain unexplored. Using an experimental post-test-only control group design, this study aimed to assess the possible additive effect of SH-MSC and alkaline water on the expression of GLUT4 and FOXO1 in Wistar rats with type 2 diabetes. Twenty-five male Wistar rats were split into five groups: healthy control (G1), T2DM control (G2), T2DM with metformin (G3), T2DM with SH-MSC (G4), and T2DM with SH-MSC and alkaline water (G5). Streptozotocin and nicotinamide were utilized to induce T2DM, and qRT-PCR was used to measure the expression of GLUT4 and FOXO1 in pancreatic tissue. One-way ANOVA and a post hoc LSD test were used for statistical analysis. The findings recognized that while GLUT4 expression was decreased, T2DM induction markedly increased fasting blood glucose levels and FOXO1 expression. SH-MSC treatment significantly upregulated GLUT4 and downregulated FOXO1 equated to the control T2DM group, and while the addition of alkaline water showed a further trend of improvement, this difference was not statistically significant. These findings suggest that SH-MSC therapy effectively improves glucose metabolism by modulating GLUT4 and FOXO1 expression, with the potential for alkaline water as an adjunctive therapy in T2DM management